2012
DOI: 10.2174/1874447801206010011
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the Comparison of Telephone and Internet Surveys for Respondent Recruitment

Abstract: Abstract:Internet surveys have a potential use for survey research when compared against costs and declining response rates of traditional modes as they form a powerful tool for reducing respondents' burden in complex questionnaires. On the other hand, there exists scepticism about the reliability and robustness of the collected data. Arenze et al. (2005) argue that case studies involving Internet surveys cannot be generalised to other countries and have recommended systematic collection and reporting of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The decision of carrying out the survey by telephone was based on the fact that this was the unique source of contact to the participants. Surveys carried out by telephone have proven better response rates compared to internet surveys [24,25]. In order to allow for non-response a total of 7,282 telephone numbers (landline and mobile) were obtained from the selected CESFAM.…”
Section: Data Collectionmentioning
confidence: 99%
“…The decision of carrying out the survey by telephone was based on the fact that this was the unique source of contact to the participants. Surveys carried out by telephone have proven better response rates compared to internet surveys [24,25]. In order to allow for non-response a total of 7,282 telephone numbers (landline and mobile) were obtained from the selected CESFAM.…”
Section: Data Collectionmentioning
confidence: 99%
“…This survey method was chosen due to applicable pandemic measures, because no face-to-face interviews were possible due to the contact restrictions. Nevertheless, personal contacts via telephone were chosen in order to obtain as many participants as possible, as it is known that response rates in online surveys are generally lower than in telephone interviews [ 23 ]. In addition, informed consent was collected and recorded verbally to make the process simple for participants and to obtain the informed consent, as face-to-face contacts were not possible due to pandemic measures.…”
Section: Methodsmentioning
confidence: 99%
“…Fan and Yan [23] suggest that response rates are influenced by various characteristics of the web survey design itself, such as topics, length, ordering and formatting. In addition, Potoglou et al [24] found that recruitment method and sampling methods significantly affect non-response rates.…”
Section: Survey Developmentmentioning
confidence: 99%